SUN-LB007 The Mouse AgRP Gene Has Three Promoters: Differential Regulation by Nutritional States - Ifebi, Bruno (J Endocr Soc, 2019)
Diabetes and obesity are metabolic indicators of an energy imbalance in the melanocortin system. Agouti related protein (AgRP) neurons in the arcuate nucleus of the hypothalamus regulate energy through the release of its neuropeptide- AgRP, along with Neuropeptide Y and GABA. AgRP acts on melanocortin 4 receptor (MC4-R) by stimulating appetite and decreasing energy expenditure. Overexpression of AgRP is known to contribute to the development of diabetes and obesity. Expression of the Agrp gene is regulated by weight loss, presumably via leptin. We found that the Ensembl database specifies that for the mouse Agrp gene there are three AgRP transcripts which differ in their 5’ untranslated regions and share the same coding exons. To determine if the AgRP mRNA isoforms are relevant for weight control, we collected tissue samples from adult mouse hypothalamus, and designed a quantitative PCR assay for each of the three AgRP mRNA isoforms. After establishing the presence of each isoform in the hypothalamus, we used these assays to determine the influence of fasting on the expression levels of the three different AgRP transcripts. We also sought to determine whether the sequences upstream of each of the three isoforms could function as promoters to drive gene expression. To determine if each upstream region can act as a promoter, we cloned the upstream regions into a reporter plasmid expressing FLAG-tagged red fluorescent protein. Each promoter construct was transfected into a neuronal cell line established from NPY/AgRP-GFP neurons. We found that all three AgRP mRNA isoforms are expressed in the adult mouse hypothalamus. While fasting caused an induction of the total AgRP mRNA (fed=1.00, fasted= 6.29; p<0.05), only AgRP-A mRNA was similarly induced by fasting (fed= 1.09, fasted=3.39 p<0.05). Surprisingly, AgRP-B and AgRP-C are not influenced by fasting. The transfection studies demonstrated that each of the upstream regions can drive expression of a reporter cassette, verified by immunofluorescence and western blot. These results indicate that studies of AgRP expression should be re-examined to take into account the complexity of Agrp gene expression. We believe that the identification of these three AgRP regulatory regions with differential expression could provide tools for understanding the regulation of Agrp gene expression by nutritional state and stress. Unless otherwise noted, all abstracts presented at ENDO are embargoed until the date and time of presentation. For oral presentations, the abstracts are embargoed until the session begins. Abstracts presented at a news conference are embargoed until the date and time of the news conference. The Endocrine Society reserves the right to lift the embargo on specific abstracts that are selected for promotion prior to or during ENDO.